2015
DOI: 10.1007/s00406-015-0663-4
|View full text |Cite
|
Sign up to set email alerts
|

Inverse effect of the APOE epsilon4 allele in late- and early-onset Alzheimer’s disease

Abstract: In Alzheimer's disease patients (AD), the age at onset (AAO) ranges from 40 to 90. Usually, AD patients who develop symptoms before the age of 65 are classified as early onset (EO). The best known genetic risk factor for AD is the ε4 allele of the apolipoprotein E (APOE). In this study, 474 subjects with AD were consecutively recruited in the memory clinic of the Santa Lucia Foundation in Rome. The best fitting model  for the discrimination between EO and late onset (LO) was chosen based on lowest value of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
1
13
0
2
Order By: Relevance
“…We observed that APOE e4 anticipates onset only in a homogeneous group of LOAD, while on the other hand the same allele did not show anticipation in EOAD [2]. However, the relationship between the e4 allele and AAO across different homogenous groups has not yet been replicated using appropriate statistics.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…We observed that APOE e4 anticipates onset only in a homogeneous group of LOAD, while on the other hand the same allele did not show anticipation in EOAD [2]. However, the relationship between the e4 allele and AAO across different homogenous groups has not yet been replicated using appropriate statistics.…”
Section: Introductionmentioning
confidence: 59%
“…Usually, AD patients who develop symptoms before the age of 65 are considered early-onset AD (EOAD) [1]; however, the majority of patients develops AD symptoms after 65, namely late-onset AD (LOAD). In our previous publication [2], we observed that the AAO in AD is not normal and can be better explained as a mixture of two normal distributions comprising EOAD and LOAD (Fig. 1a).…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Studies of LOAD suggest that the duration of illness tends to be longer in people who have a positive family history or in carriers of the APOE4 allele. However, it has since been shown that this relationship no longer holds true once the confounding effects of AAO have been taken into account [117]. Thus, in LOAD, increased survival is more directly related to an earlier AAO, which is influenced by a number of factors that are not exclusively genetic.…”
Section: Disease Durationmentioning
confidence: 99%